1980
DOI: 10.1007/bf00432641
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of skeletal muscle: Principles of reaction patterns and histochemistry and experience with 195 biopsies

Abstract: Technique and interpretation of muscle biopsies require the coordinated team work between referring clinician, surgeon, and pathologist so that optimal management of a patient with neuromuscular disease may be attained. Investigation of muscle diseases has advanced so much with an interdisciplinary approach that not only can accurate diagnosis be offered for the benefit of the patient in certain instances, but also genetic counselling provided and pre-natal diagnosis established. The principal reaction pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…While we did not observe a significant increase in centrally located myonuclei in ST TA myofibers, our results clearly indicated that there was an accumulation of nuclei around the myofibers ( Fig. 2A), which may indicate inflammatory cells infiltrate the stromal space during atrophy (32,33). The significant rise in the levels of Sca-1-positive cell population suggested that there was an increase in the density of mesenchymal and inflammatory cells in the myofibers (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…While we did not observe a significant increase in centrally located myonuclei in ST TA myofibers, our results clearly indicated that there was an accumulation of nuclei around the myofibers ( Fig. 2A), which may indicate inflammatory cells infiltrate the stromal space during atrophy (32,33). The significant rise in the levels of Sca-1-positive cell population suggested that there was an increase in the density of mesenchymal and inflammatory cells in the myofibers (Fig.…”
Section: Discussionmentioning
confidence: 52%